Islam in Global History: By Nazeer Ahmed (Concord, California: American Institute of Islamic History and Culture, 2000. 861 pages.) (American Journal of Islam and Society, 2002)
Islam in Global History, written in two volumes covering the period fromthe death of the Holy Prophet to the First World War, has the distinction ofbeing a book on history and the philosophy of history. This is because, as thereader discovers, it is not merely a chronicle of events of the Muslim worldfrom the advent of Islam to the end of the World War I; it is a book whichprovides insights into the causes of the victories and defeats of dynasties aswell as successes and failures of movements in Islamic history, and laysdown the laws for the rise and fall of civilizations.Certainly, he is not the first in the field of the philosophy of history. Thetwo stalwarts who made original and remarkable contributions in this fieldduring the last two millennia are Ibn Khaldun and Arnold Toynbee. Thebooks in which they propounded their theories of the interpretation of historyare not books on history as such. Historical data were, no doubt, usedand analyzed to substantiate their theses. lbn Khaldun proved his conceptof asabiyah (social group cohesion) in the context of the history of theArabs and the Berbers, which he was to write subsequently. Toynbee usedthe data from world history to prove his idea of "Challenge and Response"to be the detennining factor in the strength and decay of civilizations andsocieties. It is to the author's credit that such a comprehensive and coherentwork on Islamic history has been produced. At each critical stage hediagnosed the causes of the major events that went into making watershedsand turning points in Muslim history worldwide.Dr. Ahmed is an eclectic writer who has partially benefited from theconcepts of the interpretation of history expounded by lbn Khaldun andToynbee. For example, he agrees with lbn Khaldun when he says:The origins of the Ottoman Empire are to be found in a combination ofTurkish 'asabiyah, a term used by lbn Kha Idun to denote tribal cohesion,the force that holds together tribes through bonds of blood, a characteristicfound in abundance among peoples of the desert and the nomads offthe steppes.He concurs with Toynbee when he writes:Great civilizations measure up to their challenges and grow more resili entwith each crisis, turning adversity into opportunjty. Critical moments in ...